Pannus growth regulators as potential targets for biological therapy in rheumatoid arthritis - A. S. Mikhaylova; O. M. Lesnyak (Современная ревматология)
The main goal of treatment for rheumatoid arthritis (RA) is to suppress inflammation using basic and symptomatic therapies. At the same time, the above strategy does not significantly stop joint  destruction that leads to disability in patients. The review analyzes  publications dealing with a search for intercellular interaction  regulators among the main effector cells in the pannus – fibroblast- like synoviocytes (FLSs). It assesses the influence of FLS aggression  factors on invasive pannus behavior, the possibility of their targeted deactivation during biological therapy, and the preliminary  results of similar treatment by the examples of animal models. It is  shown that the most promising targets for biological therapy may be FLS adhesion molecules, such as transmembrane receptor cadherin  11, integrins α5/β1, and VCAM1, ICAM1, which actively participate in the attachment of FLSs to the cartilage surface and activate their production of cytokines, growth factors and aggression factors.